Gender inequalities in ownership and control of land - Kieran, Caitlin; Doss, Cheryl (2016)
Collection of pie charts compiled by Caitlin Kieran (IFPRI) and Cheryl Doss (Yale) in honor of "Pi Day" on March 14, 2016. These slides appeared in a blog story on the CGIAR Research Program on Policies, Institutions, and Markets (PIM) EnGendering Data blog at https://www.pim.cgiar.org/2016/03/14/celebrating-pi-day-what-pie-charts-can-tell-us-about-gender-gaps-in-control-over-land/